Effectiveness of Porous Durian Shell-based Activated Carbon for Methylene Blue Adsorption - Mohamat, Rosmanisah; Abu Bakar, Suriani; Mohamed, Azmi; Kamari, Azlan; Muqoyyanah; Othman, Mohd Hafiz Dzarfan; Mamat, Mohamad Hafiz; Ahmad, Mohd Khairul; Mohammad Noorazlan; Hashim, Norhayati; Mohamed, Mohd Ambri; Birowosuto, Muhammad Danang; et al. (International Journal of Integrated Engineering, 2024)
In this study, durian shell-based activated carbon (DAC) was produced via chemical activation method by utilising durian shell and sulphuric acid (H2SO4) as the starting material and activating agent, respectively. The incorporation of H2SO4 in the DAC production process resulted an improvement in the surface properties and adsorption capacity of the produced DAC adsorbent. Field emission scanning electron microscopy analysis further showed that the produced DAC possessed a porous structure which was beneficial for dye adsorption application. Under operating conditions of 500°C and 3 hours carbonisation temperature and time, the Brunauer–Emmett–Teller (BET) surface area, total pore volume and BET average pore diameter were measured to be 242.03 m2/g, 0.028 cm3/g and 2.28 nm, respectively. The adsorption performance of the produced DAC was then investigated using methylene blue (MB) as the model adsorbate. The optimum MB dye removal and adsorption capacity were found to be 92.05% and 0.767 mg/g, respectively, with 0.6 g of DAC dosage, 10 ppm of initial MB dye concentration and 15 min of contact time.